2021
DOI: 10.1016/j.jbc.2021.100913
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of aminoacyl-tRNA synthetases from trypanosomatids

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Apart from the technical considerations, our observations raise the question of the functional significance of the presence of this stem-loop structure at the extremity of all C. elegans SL variants. It has been previously observed that potential stem-loop structures adjacent to the cap are widespread in the Spliced Leaders of phylogenetically divergent species although the sequence of the self-complementarity itself is not conserved 24 . We confirmed the same strand bias in Leishmania Tarentolae direct-cDNA sequencing experiments 24 , and it is likely that similar library behavior will extend to all species using trans -splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the technical considerations, our observations raise the question of the functional significance of the presence of this stem-loop structure at the extremity of all C. elegans SL variants. It has been previously observed that potential stem-loop structures adjacent to the cap are widespread in the Spliced Leaders of phylogenetically divergent species although the sequence of the self-complementarity itself is not conserved 24 . We confirmed the same strand bias in Leishmania Tarentolae direct-cDNA sequencing experiments 24 , and it is likely that similar library behavior will extend to all species using trans -splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the structures of HF-bound Pf ProRS and Hs ProRS are identical, there are substantial differences in the interaction of some of the residues such as Thr478, terminal phosphate group of AMPPNP, water molecule, etc., which suggest that inhibitors of Pf ProRS, like quinazolinone, might also inhibit trypanosomal ProRS. Both cytosolic and mitochondrial ProRS isoforms in Leishmania contain the Ybak/ProX domain at the N-terminus (Figure ), which is a prokaryotic-type editing domain and helps in the rectification of mischarged tRNAs. , …”
Section: Research Accomplished On Trypanosomatid Aminoacyl Trna Synth...mentioning
confidence: 97%
“…In T. brucei , the lysyl tRNA synthetases are located in mitochondria as well as cytosol, and these isoforms are coded by distinct genes. 45 The mitochondrial LysRS has a C-terminus extension of 92–96 amino acids 46 ( Figure 4 ). In humans, LysRS was found to have a very strong interaction with multi-aaRSs complex (MARS).…”
Section: Research Accomplished On Trypanosomatid Aminoacyl Trna Synth...mentioning
confidence: 99%
See 2 more Smart Citations